Promoting cognitive and emotional adjustment well of Nigerian children: critical issues for early childhood teacher education (2016)
Preschool children could be helped to make early adjustment to a school environment before normal schooling begins. Transition from home to school represents one of the biggest changes that children undergo in the first eight years of life. This change may be likened to that which a seedling undergoes when transplanted from one place to another. Thus, those working with children should seek ways to minimize the shock and increase opportunities to aid quick stabilization. The ability to achieve this may not be a chance factor but a function of some school and some home factors. This study, therefore, investigated how levels of parental involvement and school factors aid in promoting children’s emotional and cognitive adjustment to school. Six out of eleven predictor variables contributed significantly to the variance in the factors influencing the adjustment of children at the nursery school setting.